2022
DOI: 10.3390/antibiotics11060725
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Antibiotic-Resistance, and Replicon-Typing of Salmonella Strains among Serovars Mainly Isolated from Food Chain in Marche Region, Italy

Abstract: Nontyphoidal salmonellosis (NTS) is the second most commonly reported gastrointestinal infection in humans and an important cause of food-borne outbreaks in Europe. The use of antimicrobial agents for animals, plants, and food production contributes to the development of antibiotic-resistant Salmonella strains that are transmissible to humans through food. The aim of this study was to investigate the presence and the potential dissemination of multidrug-resistant (MDR) Salmonella strains isolated in the Marche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…With the introduction of PCR-based replicon typing (PBRT; Russo et al, 2022 ), more IncA and IncC plasmids were identified in bacterial species. This study used available IncA and IncC plasmid sequences to revise core functional gene sets and backbone evolution and comprehensively characterised the essential modules of these plasmids, such as the conjugative transfer system and all MGEs embedded in comparison with SXT/R391.…”
Section: Introductionmentioning
confidence: 99%
“…With the introduction of PCR-based replicon typing (PBRT; Russo et al, 2022 ), more IncA and IncC plasmids were identified in bacterial species. This study used available IncA and IncC plasmid sequences to revise core functional gene sets and backbone evolution and comprehensively characterised the essential modules of these plasmids, such as the conjugative transfer system and all MGEs embedded in comparison with SXT/R391.…”
Section: Introductionmentioning
confidence: 99%
“…With the introduction of PCR-based replicon typing (PBRT) (Russo et al, 2022), more IncA and IncC plasmids were identi ed in bacterial species. This study used available IncA and IncC plasmid sequences to revise core functional gene sets and backbone evolution and comprehensively characterised the essential modules of these plasmids, such as the conjugative transfer system and all MGEs embedded in comparison with SXT/R391.…”
Section: Introductionmentioning
confidence: 99%